Theoretical studies of high-power laser beam smoothing via stimulated brillouin scattering in plasma - Yuan, Hang; Hao, Jianing; Dan, Ziqiang; Zhu, Chengyu; Li, Yuxin (Frontiers in Physics, 2022)
To achieve uniform irradiation, the focal spot from a high-power laser system must be homogeneous; thus, laser beam smoothing is required. In this study, we theoretically demonstrated a novel spatial smoothing method based on stimulated Brillouin scattering (SBS) in a plasma. As SBS is sensitive to pump intensity, the area of higher intensity in the laser beam has a higher reflectivity, leading to a more homogeneous passed beam. From the theoretical simulation, the laser beam modulation significantly decreased in SBS, while the fluence contrast decreased from 15.9% to 9.7%.